Gambaran Self-esteem pada Anak Usia 9-12 Tahun - Khansa Mujahidah; Indri Utami Sumaryanti (Jurnal Riset Psikologi, 2025)
Abstract. Self-esteem develops throughout an individual's life and is influenced by various factors. To optimize the development of self-esteem, a clear understanding of its current condition is necessary. This study aims to describe self-esteem in children aged 9-12 years. The research employs a descriptive method with a quantitative approach. The population consists of elementary school students in grades IV, V, and VI, aged 9-12 years. The sample was selected using the convenience sampling technique, with the Rosenberg Self-esteem Scale (RSES) as the instrument. Data analysis was performed using descriptive statistics and paired-sample u-tests. The findings indicate that self-esteem in children aged 9-12 years can be classified into three categories: low, moderate, and high. The majority of children fall within the moderate to high categories, suggesting no significant issues with self-esteem. Additionally, the analysis of the two dimensions of self-esteem reveals that self-liking is higher than self-competence. This depiction of self-esteem in children aged 9-12 years can serve as a reference for developing interventions aimed at enhancing children's self-esteem. Abstrak. Self-esteem berkembang sepanjang kehidupan seseorang dan dipengaruhi oleh berbagai faktor. Untuk mengoptimalkan perkembangan self-esteem, diperlukan pemahaman yang jelas mengenai kondisinya. Penelitian ini bertujuan untuk menggambarkan self-esteem pada anak usia 9-12 tahun. Penelitian ini menggunakan metode deskriptif dengan pendekatan kuantitatif. Populasi penelitian terdiri dari siswa kelas IV, V, dan VI sekolah dasar yang berusia 9-12 tahun. Sampel dipilih menggunakan teknik convenience sampling dengan instrumen kuesioner Rosenberg Self-esteem Scale (RSES). Analisis data dilakukan menggunakan teknik analisis deskriptif dan uji u-berpasangan (paired-sample u-test). Hasil penelitian menunjukkan bahwa self-esteem anak usia 9-12 tahun terbagi ke dalam tiga kategori: rendah, sedang, dan tinggi. Mayoritas anak berada pada kategori sedang hingga tinggi, yang menunjukkan tidak adanya masalah serius terkait self-esteem. Selain itu, analisis dua dimensi self-esteem menunjukkan bahwa dimensi self-liking lebih tinggi dibandingkan dengan self-competence. Gambaran mengenai self-esteem pada anak usia 9-12 tahun ini dapat dijadikan literatur pendukung dalam merancang intervensi yang bertujuan meningkatkan self-esteem anak.